Pengaruh Metode Ultrasound Assisted Extraction (UAE) terhadap Kadar Antosianin dan Aktivitas Antioksidan Ekstrak Beras Hitam (Oryza sativa L. indica) - Novi Alfi Ramadhani; Danang Raharjo; Bangkit Riska Permata (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Black rice (Oryza sativa L. indica) is one of the natural sources of anthocyanins with high potential as an antioxidant to neutralize free radicals. This study aimed to further evaluate the effect of the Ultrasound Assisted Extraction (UAE) method on anthocyanin content and antioxidant activity of black rice extract. The extraction process was carried out using 70% ethanol acidified with 1% HCl at a material-to-solvent ratio of 1:15 (w/v), with an ultrasonic frequency of 42 kHz for 30 minutes under controlled conditions. Total anthocyanin content was determined using the pH differential method, while antioxidant activity was analyzed using the ABTS method to determine the IC₅₀ value.The results showed an extract yield of 17.8%, reflecting the efficiency of the extraction process. The total anthocyanin content obtained was 236.43 mg/100 g sample. The antioxidant activity showed an IC₅₀ value of 68.71 ppm, which is categorized as strong activity. Phytochemical screening confirmed the presence of alkaloids, flavonoids, anthocyanins, tannins, saponins, and triterpenoids that contribute to the biological activity of the extract. Overall, these findings indicate that the UAE method effectively enhances the extraction efficiency of bioactive compounds from black rice and produces extracts with high anthocyanin content and antioxidant capacity, making it a promising natural antioxidant source for functional food and health products.